Yield line analysis of two way reinforced concrete slabs with corner opening - Part II: Design tables and application - Kumar V.; Nautiyal B.D.; Choudhary R.K. (My University, 2025)
The yield line analysis of reinforced concrete rectangular slabs for different boundary conditions with corner opening had been carried out in Part I of this paper. The ratios of the corresponding lengths of the sides of the opening and the slab are kept the same and the size of opening upto half of the length of the slab sides are considered. The ratio of the span moments to support moments is kept equal to 0.75. The design tables and the examples to explain the use of the tables for analysis of slab are presented in this paper.